2018
DOI: 10.5530/jppcm.2018.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-managed Diabetes Clinic in Malaysia - Does the Number of Follow-up Visits Really Matter?

Abstract: Background: The involvement of pharmacists in diabetes education and management has been shown to improve patient outcomes worldwide. The pharmacist-managed Diabetes Medication Therapy Adherence Clinic (DMTAC) has been introduced across public healthcare settings in Malaysia to enhance patient adherence to treatment. Objective: This study was designed to assess the effectiveness of the DMTAC in optimizing the glycemic control of diabetic patients, and to subsequently identify the relationship between the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…This study revealed a significant HbA1c reduction among diabetic patients after DMTAC visits. This was in line with two small-scale Malaysian studies conducted in a health clinic and a tertiary hospital, which demonstrated a smaller degree but significant HbA1c reduction [ 15 , 16 ]. Within expectations, we observed that patients who did not default from follow-up achieved a significantly lower level of HbA1c in both time points than defaulters.…”
Section: Discussionsupporting
confidence: 88%
“…This study revealed a significant HbA1c reduction among diabetic patients after DMTAC visits. This was in line with two small-scale Malaysian studies conducted in a health clinic and a tertiary hospital, which demonstrated a smaller degree but significant HbA1c reduction [ 15 , 16 ]. Within expectations, we observed that patients who did not default from follow-up achieved a significantly lower level of HbA1c in both time points than defaulters.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to the prospective Randomized Control Trials (RCTs), retrospective research studies also presented similar results. Abdullah et al ( 17 ) conducted a study that showed that the average decrease in HbA1c in diabetic patients was improved by 1.32% due to collaborative care by pharmacists. However, another study by You et al ( 18 ) presented the results that the average decrease in HbA1c with the contribution of pharmacists is 1.0% with a standard deviation of ±1.7.…”
Section: Discussionmentioning
confidence: 99%